The biology of the abalone Haliotis Midae - Newman, G. G (Department of Biological Sciences, 2023)
The abalone Haliotis midae is commercially exploited in South Africa. A maximum production of canned abalone was attained in 1965, when about one point five million lbs. were produced. Subsequently the catch has declined, due to overfishing, and in 1968 canned production fell to about seven hundred thousand lbs. The Division of Sea Fisheries is responsible for managing the exploitation of marine stocks in South Africa. To do this effectively, data are required on the general biology and population dynamics of the stocks concerned. Apart from some notes on distribution (Stephenson 1944) no information was available on Haliotis midae. In 1962 the Division therefore started research on the biology of Haliotis midae, to provide an essential basis for later stock assessment. This thesis dee.ls with three aspects of the above programme, that is reproduction, growth and movement. The first two topics are presented in the form of Investigational Reports published by the Division of Sea Fisheries. The section on movement is based on the findings of a more detailed paper by the candidate which was also published as an Investigational Report.